The Influence Of Teacher Competency On Teacher Performance At Vocational School 2 Lubuklinggau With Motivation As Intervening Variables - Sulasji*, Astri Riance; Herlina, Herlina; S, Sinta; Deviyant, Youlori (Universitas Syiah Kuala, 2023)
The title of this study was The Effect of Teacher Competence on Teacher Performance at SMK Negeri Number 2 Lubuklinggau with Motivation as an Intervening Variable. The problem in this research were teachers who have not conducted research or made scientific work. Teachers not used learning media. In collecting the data this study used observation, questionnaires and documentation. The results showed that teacher competence had an effect on teacher performance at SMK Negeri Number 2 Lubuklinggau, this was shown by the value of t count being greater than t table, it was 4,946 lb 0.680. Teacher competence has a significant effect on teacher performance at SMK Negeri Number 2 Lubuklinggau with motivation as the intervening variable. Directly teacher competence through motivation has a significant influence on teacher performance. It can be seen from the direct influence value of 0.611 which was greater than the indirect effect value of 0.125. Motivation can also be a mediator between teacher competence and teacher performance, as evidenced by the statistical test score of 1.831 greater than 1.96.